Psychoeducation in impproving psychological support for caregiver of chilhood cancer: literature review - Laila Nidaul Hasanah; Allenidekania Allenidekania (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Cancer is one of the main causes of death in the world, especially in developing countries. Cancer is not only a problem for adults but also a major health problem in children. Cancer in children is a chronic disease and responds to parents/caregivers. Psychological and emotional responses cause psychological problems and stress in parents/caregivers. One of the interventions to reduce psychological problems is psychoeducation. Family psychoeducation is a  modality of therapy with the focus of treatment on the family. Objectives: To know various psycho-educational techniques and their impact on increasing caregiver psychological support Methods: The research method used is a literature review using the Proquest, Pubmed, Google Scholar, and Science Direct databases, with the keywords caregiver or parent or family and pediatric cancer or childhood cancer and psychoeducation or psychosocial and psychological support. Results: This study provides diversity in providing psychoeducation to caregivers with cancer children. Various techniques are used in the form of positive thinking, cognitive therapy, and brief therapy, educational and psychosocial techniques. The various techniques used have a positive impact on reducing anxiety, depression, stress, and trauma, improving coping strategies and quality of life, and increasing family resilience.Conclusions: Psychoeducation is a nursing intervention that can be given to caregivers with childhood cancer. Psychoeducation is given to caregivers to improve the ability to care for patients and increase psychological support.